The role of competitive advantage and the strength of good corporate governance in supporting the influence of knowledge management on company performance - Purwoko, Bayu Hatmo; Sumiati, Sumiati; Ratnawati, Kusuma; Aisjah, Siti (Edelweiss Applied Science and Technology, 2025)
This study investigates the role of competitive advantage and the moderating effect of good corporate governance (GCG) in enhancing the impact of knowledge management on organizational performance within PT Angkasa Pura II, a state-owned airport enterprise in Indonesia. Guided by the Resource-Based View (RBV) framework, this research adopts a quantitative explanatory design. Data were collected from 198 senior leaders and managers across 20 airports operated by PT Angkasa Pura II and analyzed using Structural Equation Modeling (SEM). The findings reveal that knowledge management exerts a positive yet insignificant influence on competitive advantage, while competitive advantage significantly improves organizational performance. Furthermore, GCG strengthens the relationship between competitive advantage and organizational performance, demonstrating its strategic role in enhancing sustainable performance outcomes. The study highlights the critical integration of knowledge management and governance practices in building and sustaining organizational competitiveness. The results provide practical insights for managers and policymakers in state-owned enterprises to align knowledge management strategies with good governance principles for long-term organizational success.